Carbonatação em concreto com cinza de casca de arroz sem moagem - Hoppe, Alessandro Eduardo (2008)
This research is part of a project that aimed to evaluate the technical viability of the use of unground (in natura) residual Rice Husk Ash (RHA), without grinding, for structural concrete. The present work investigated the evaluation of the depth and the determination of the carbonation coefficients for concrete with the addition of 15% and 25% residual RHA in replacement of cement CP II F-32 (values in mass) ground in mill of balls and unground, and compared with the reference concrete with three water/cimenticious materials ratios: 0.45, 0.55 and 0.65. This work aimed more specifically to analyze the influence of the type and the level of residual RHA incorporated to the concrete on the carbonation process. Accelerated carbonation, mercury intrusion porosimetry and remaining calcium hydroxide level were investigated. For comparison, axial compression strength tests were carried out. The accelerated carbonation tests were performed after a period of 3, 6, 9 and 12 weeks of exhibition to CO2 in climatic chamber. Porosimetry, remaining calcium hydroxide, and axial compression strength tests were performed on 91 days. The results showed that the carbonation coefficients of the ground residual RHA sample were lower than the values presented by the unground (in natura) residual RHA, in both replacement levels and in all water/cimenticious materials ratios. The lowest carbonation coefficient values were related to the reference concrete. Concerning mercury intrusion porosimetry, the incorporation of RHA caused a refinement of the concrete pores when compared to the reference in the three water/cimenticious materials ratios used. On the other hand, the effect of the lowest alkaline reservation of the concretes containing the incorporation of residual RHA prevailed on the effect of the permeability reduction of the concretes caused by the addition of RHA. Therefore, the use of residual RHA to the structural concrete in levels of 15% of incorporation to ground and in natura samples in the water/cimenticious materials ratios 0.45, 0.55 and 0.65; in levels of 25% of replacement for the in natura sample of water/cimenticious material ratios 0.45, as well as the ground sample with water/materials cimenticious ratios 0.45 and 0.55, is an option when carbonation is the main variable of concrete durability.